Evaluation of the National Skin Cancer Campaign: a Swiss experience of Euromelanoma (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY Skin cancer is a burden to healthcare and patients worldwide. The incidence of skin cancer has been rising during recent decades and this trend is expected to continue in the future. Numerous risk factors have been identified and prevention strategies developed. The Euromelanoma campaign is a pan-European skin cancer prevention programme, targeted to both primary and secondary prevention of malignant melanoma. The current study aimed to evaluate the results of the Swiss skin cancer screening day 2016. METHODS A questionnaire was used to obtain data on characteristics and suspected skin cancers of all participants. Follow-up of patients with suspicious lesions was performed 3 to 6 months later. RESULTS During the campaign, 2795 people were screened. Of the screened individuals, 157 participants (58% female, 42% male; mean age 58.8 years) underwent further evaluations; 6 cutaneous malignant melanomas, 21 basal cell carcinomas and 2 squamous cell carcinomas were detected. Detection rates were 0.21% for cutaneous melanoma, 0.75% for basal cell carcinoma and 0.07% for squamous cell carcinoma. CONCLUSIONS Our study provides an up-to-date evaluation of the Swiss Euromelanoma campaign 2016. The results are mostly in line with data from other European studies. Considering the morbidity, mortality and financial and social impact of skin cancer, the capacity to raise awareness of risk factors, skin cancer prevention methods and educating high-risk and at-risk individuals, we may assume that a National Screening Day has a crucial impact on the public health system.